The influence of processing temperature on the mechanical properties of recycled PET fibers - Fauza, Anna Niska; Qalbina, Fitrah; Nurdin, Hendri; Ambiyar, Ambiyar; Refdinal, Refdinal (Universitas Negeri Padang, 2023)
Study towards the recycling of PET waste has arisen in the last decades. One of the most widely used methods was the mechanical recycling process due to its simplicity and low cost of production. In this research, PET waste obtained from the disposable water gallon containers was used to produce recycled PET fibers for textile applications. The PET fibers were prepared using the extrusion technique by varying the processing temperatures, i.e., 200, 210, 220, 230, and 240°C. The diameter, FTIR analysis, XRD analysis, and mechanical properties of the PET fibers at various processing temperatures were studied. The results showed that the optimum processing temperature for preparing recycled PET fibers was 210°C with a diameter of 0.23 mm, a degree of crystallinity of 8.9%, a tensile strength of 70.4 MPa, and an elongation at break of 83.6%. In conclusion, PET waste shows a promising application to be processed as recycled PET fibers for textile applications.